Strategy of PV distributor - Adrián, Michal (2014)
The goal of this work is to redefine strategy of Czech photovoltaic distributor, which is currently entering new foreign markets and launching new products. The theoretical part of thesis describes generic strategies, main theoretical schools of internationalization, and entry modes to foreign markets, industry and market analysis tools, and types of international companies. The practical part consists of internal and external analysis. Internal analysis describes company background, products, customers, competitors and contains SWOT analysis. External analysis describes PV industry and development of European market. Final part of practical section is proposal of new strategy. The outcome of thesis is that Solarity should follow differentiation strategy with appropriate competitive focus. Proposal emphasizes several new sources of competitive advantage. Preferred country list with appropriate entry mode is also proposed.